Os Saberes Locais e o novo Currículo do Ensino Básico - Basílio, Guilherme (2006)
The paper discusses the local knowledge and the new curriculum of Basic Education with the aim of rescuing it to School. This discussion is supported by the institutionalization of local curriculum which opens possibility of integrating the local contents and practices in the education programs. The reason for integrating the local curriculum in to the education programs is to reduce the distance between two cultures; the modern School and the local traditional. The new curriculum of Basic Education integrate a local curriculum component to create relevant learning and for rescing local knowledge to School. This thesis supports the idea that the schools must rescue autochthonou s culture and its intrinsic values. It is argued that the inclusion of local knowledge in the school can facilitate the learning process and contextualize the local socio-cultural conditions. With the introduction of local curriculum a local knowledge a sociability space is open and a challenge is launched to the teachers in order to take responsibility in the production and systematization of knowlodge. The theoretical support for this work is based on the curriculum theory of Moreira and Silva (2002) as well as the theses of Geertz (1997) and Gramsci (2004). The empiric material was collected based on the reports of INDE documents (1999 2004). The need to better the learning in schools and to set students in their cultural perspective brought transformation for Mozambican curriculum of Basic Education. From the curricular reformation the research gave priority to perception about the local knowledge and assesses the method of integration of relevant local contents and practices in the target schools located in Nampula province. Lessons were observed with the objective of evaluating this process of integrating local knowledge into new curriculum. In addition to interview with teachers, students and the community people s views about their culture were also collected for their integration into the Basic Education curriculum.